An Electronic Health Record–based Intervention to Promote Hepatitis C Virus Testing Among Adults Born Between 1945 and 1965: A Cluster-randomized Trial. Issue 6 (June 2017) - Federman, Alex D.; Kil, Natalie; Kannry, Joseph; Andreopolous, Evie; Toribio, Wilma; Lyons, Joanne; Singer, Mark; Yartel, Anthony; Smith, Bryce D.; Rein, David B.; Krauskopf, Katherine
Abstract : Background: The Centers for Disease Control and Prevention (CDC) recommends one-time hepatitis C virus (HCV) antibody testing for "Birth Cohort" adults born during 1945–1965. Objective: To examine the impact of an electronic health record (EHR)-embedded best practice alert (BPA) for HCV testing among Birth Cohort adults. Design: Cluster-randomized trial was conducted from April 29, 2013 to March 29, 2014. Subjects and Setting: Ten community and hospital-based primary care practices. Participants were attending physicians and medical residents during 25, 620 study-eligible visits. Intervention: Physicians in all practices received a brief introduction to the CDC testing recommendations. At visits for eligible patients at intervention sites, physicians received a BPA through the EHR to order HCV testing or medical assistants were prompted to post a testing order for the physician. Physicians in control sites did not receive the BPA. Main Outcomes: HCV testing; the incidence of HCV antibody positive tests was a secondary outcome. Results: Testing rates were greater among Birth Cohort patients in intervention sites (20.2% vs. 1.8%, P <0.0001) and the odds of testing were greater in intervention sites after controlling for imbalances of patient and visit characteristics between comparison groups [odds ratio (OR), 9.0; 95% confidence interval, 7.6–10.7). The adjusted OR of identifying HCV antibody positive patients was also greater in intervention sites (OR, 2.1; 95% confidence interval, 1.3–11.2). Conclusions: An EHR-embedded BPA markedly increased HCV testing among Birth Cohort patients, but the majority of eligible patients did not receive testing indicating a need for more effective methods to promote uptake.